Cyber security in parallel and distributed computing concepts, techniques, applications and case studies - Chatterjee, Jyotir Moy; Khari, Manju; Kumar, Raghvendra 1987-; Le, Dac-Nhuong 1983-; Mishra, Brojo Kishore 1979- (Beverly, Massachusetts Scrivener Publishing LLC, 2019)
"Covers privacy issue and challenges in data intensive cloud computing environment. Covers the concept of parallel and distributed computing technologies and their applications in real world settings. Offers data processing and security solutions Covers privacy issue and challenges in data intensive cloud computing environment. Includes the latest technologies that cover the major changes and advances of cyber security"
Includes bibliographical references and index.
Keywords: Computer security; Computer networks -- Security measures; Parallel processing (Electronic computers) -- Security measures; Electronic data processing -- Distributed processing -- Security measures